Use of Coaching by Nurses on professional practice: integrative review (Research, Society and Development, 2020)
Aim: To analyze the existing scientific literature about the use of Coaching by nurses on professional nursing practice. Methods: Integrative literature review of full texts online published from 2015 to 2019 held in July 2020 at the Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Literature in Health Sciences, Cumulative Index to Nursing and Allied Health Literature and Education Resources Information Center. Results: 33 articles are analyzed. Most are quantitative, inform an intervention and are published in qualified journals with the first author linked to the institution in the United States. The use of Coaching as a process by healthcare nurses predominates in the Health Coaching modality. 63% of the articles report some training of nurses who applied the interventions. Conclusion: A more detailled description of the processes and techniques is beneficial to the understanding of the form of use and potential dissemination. The need for specific training for nurses when using Coaching is emphasized.